Effect of the Islamic Self-care Nutrition Method on the Lipid Profile of Patients with Type 2 Diabetes: A Randomized Clinical Controlled Trial - Zakizad Abkenar , Manizheh; Ghofranipour, Fazlollah; Kashi, Zahra; Montazeri, Ali (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Dyslipidemia is one of the main risk factors of cardiovascular disease in people with diabetes. The principle of diabetes prevention and control is based on patient self-care and education. The Islamic self-care nutrition method is a common and successful way to modify behavior in Islamic ethics and mysticism. AIM: The study aimed to determine the effect of the Islamic self-care nutrition method on the lipid profile of patients with type 2 diabetes. MATERIALS AND METHODS: The present clinical trial was conducted in 2014 on 98 middle-aged patients with type 2 diabetes referred to the Diabetes Center of the Mazandaran University of Medical Sciences, Sari, Iran, who were randomly allocated into two groups of experimental and control. Lipid indices were measured before intervention, and the same education about diabetic healthy diet was provided in both groups. In addition, in the experimental group, Islamic teachings and the Islamic self-care method of nutrition were taught with the intention of pleasing God. Data were analyzed with SPSS 22 software using independent and paired t-test, Chi-square, Fisher’s exact, and analysis of covariance (ANCOVA). RESULTS: After adjusting for the effect of confounding variables with ANCOVA, significant improvement was observed in triglycerides and low-density lipoprotein indices in the experimental group after intervention compared to the control group. Two-proportion z-test results showed a significant increase in the use of lipid-lowering drugs in the control group compared with the experimental group after intervention. CONCLUSION: The Islamic self-care nutrition method could be used to control chronic diseases such as type 2 diabetes affected by behavioral factors.